Moral Framing and Legitimizing Asymmetry in Joe Biden’s Post–October 7, 2023 Israel–Palestine Rhetoric - Meyanti Nurchaerani; Alfian; Syahiid Hidayatullah Rizkika Hartadhi; Iswadi (INJECT (Interdisciplinary Journal of Communication), 2025)
The Israel-Palestine conflict had long been a focal point of global attention, drawing interest from various perspectives. Within this landscape, the speech delivered by President Joe Biden stood as a significant subject for critical examination. Employing the framework of Critical Discourse Analysis (CDA), a study dissected President Biden's speech to unravel its rhetorical elements, linguistic nuances, and the implicit impact on the Israel-Palestine conflict. The analysis discerned President Biden's articulated stance, showcasing a nuanced support for Israel while advocating a pursuit of equitable solutions for both sides involved. This investigation underscored the pivotal role of political rhetoric wielded by world leaders in navigating intricate conflicts. This research aimed to shed light on how President Biden's discourse shaped global perceptions of the Israel-Palestine conflict. Anchored in scholarly discourse and employing rigorous analysis, this study elucidated the significance of leader-speak in influencing global perspectives, especially within the context of this complex geopolitical impasse.